Kajian Ergonomika Terhadap Penggunaan Mesin Penggoreng Vacuum - Ramadhanti, Annisa Suci; Wisnu, Febryan Kusuma; Suharyatun, Siti; Warji, Warji (Jurnal Agricultural Biosystem Engineering, 2023)
Agricultural machine tools with technology can help processes in agriculture so that time is more effective, cost-effective and improves the quality or quality of plants or products, such as vacuum frying which is used to fry fruit chips that are susceptible to hot temperatures so that the taste of fruit chips from vacuum frying will be similar to the original fruit. The use of agricultural tools and machines cannot be separated from K3 and ergonomics. Therefore this research was conducted for the ergonomics of a vacuum fryer in terms of anthropometry, recommended workload, work fatigue, and the physical work environment. This study used a quantitative method supported by literature studies on the ergonomic dimensions of a vacuum fryer or in accordance with the size of the human body. The results showed that the ergonomic dimensions of the tool corresponded to the dimensions of the operator's body in the form of control box height, stove height, frying tube cover height, pressure output height, pressure regulator height, and stirrer lever. The level of operator fatigue is classified as ergonomic because the CVL (Cardiovascular Load) percentage obtained is ≤ 30% so that fatigue does not occur in operating the tool. The recommended workload is classified as ergonomic because the actual load lifted is lower than the RWL calculation results. The temperature measurement is not ergonomic because the temperature exceeds the NAV, while the lighting is classified as ergonomic because it has exceeded the minimum standard value for lighting and the noise measurement is classified as ergonomic because it does not exceed 88 dBA. In operating a vacuum fryer, it can be done in the morning or there is a work station repair so that glare does not occur when using the machine, and when using it, it must be equipped with personal protective equipment (PPE). Keywords: Anthropometry, Ergonomic, Vacuum Fryer